The effect of computational thinking on cognitive load and problem-solving skills of electrical engineering education students at Universitas Negeri Malang - Yuni Rahmawati; Alfiana Sari (Universitas Negeri Padang, 2025)
The rapid development of technology requires prospective teachers to master 21st century skills, particularly problem solving. Students in the Bachelor of Electrical Engineering Education program at Universitas Negeri Malang often experience a high cognitive load due to heavy academic demands and limited computational thinking, which hinder their problem-solving abilities. This study investigates the influence of computational thinking on cognitive load and problem-solving skills. Using a quantitative descriptive design with saturated sampling, 116 students from the 2022–2023 cohorts participated by completing a closed-ended questionnaire. Data were analysed through prerequisite tests, descriptive statistics, and hypothesis testing using MANOVA with SPSS 27. Results show that students with higher computational thinking have lower cognitive load (M = 44.19) and higher problem-solving skills (M = 55.70). Computational thinking significantly affects cognitive load (p < 0.001, η² = 0.415) and problem solving (p = 0.019, η² = 0.067). However, this study is limited to self-reported questionnaire data from a single institution, which may affect the generalizability of the findings. The novelty of this research lies in its simultaneous examination of computational thinking, cognitive load, and problem-solving skills in engineering education, an area that remains underexplored in the Indonesian higher education context. These findings indicate that computational thinking plays a substantial role in reducing cognitive load and improving problem-solving skills, thereby providing valuable insights for curriculum development and instructional design in higher education.